Financial malpractice as a destabilization factor of real financial reporting - Pavle Parnicki; Danijela Živković Petrović; Jelena Tucaković (Anali Ekonomskog fakulteta u Subotici, 2021)
In the text of this scientific research we pointed out the natural correlation between the phenomenon of undertaking manipulative actions on financial and accounting reports by corporations, in circumstances of intensification, acceleration, as well as multiplication of fiscal pressure by the representatives of the management at the macroeconomic level. Also, with explications and scientific conclusions, we pointed out the destabilizing moments of consistent implementation of the principles of corporate governance, particularly in the circumstances of actual resorting to the use of different techniques of financial malversations by corporations or microeconomic entities as well as by individual households, because, in the etymological sense, they are also accepted as microeconomic subjects. At the same time, with the technique of optical laser guidance, we marked economic barriers and in the constellation of the subject matter without tendentious finger-pointing at individuals. Exclusively, using the technique of criticizing the contaminated state, the detection of neuralgic points of inhibition of optimal economic flows was performed, analysed through the prism of the need to respect the principles of corporate management.